Concrete: A Review on Modeling Techniques of Cementitious Materials under Different Length Scales: Development and Future Prospects (Adv. Theory Simul. 7/2019). Issue 7 (1st July 2019) - Wang, Xing Quan; Chow, Cheuk Lun; Lau, Denvid
Abstract : The cover represents the concrete structure and particles in a sphere with a futuristic sense. The investigation of building materials on the nanoscale and mesoscale is the trend of the simulation. The development of cementitious materials modeling, as well as the advantages and limitations of macroscale, nanoscale, and multiscale modeling with an emphasis on the improvement of the nano‐engineering approach, and the linkage between nanoscale and macroscale are introduced in by Denvid Lau and co‐workers in article number 1900047 .